2021
DOI: 10.1590/1413-81232021267.20222019
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and risk behaviors for chronic noncommunicable diseases among healthcare undergraduates in Midwest, Brazil

Abstract: This study aimed to assess the lifestyle of undergraduate university students, and to investigate the prevalence of risk behaviors for chronic noncommunicable diseases. This cross-sectional study took place in Brasilia, with 2.163 healthcare undergraduates. We used a self-administered questionnaire for demographic variables, social class, behavioral data, self-perception of health and self-reported diseases. Given a total of 2.163 students, 69.3% were female, 65.4% were 20-29 years, men smoked more cigarettes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Among the risk behaviors for CNCDs in Brazilian university students in health courses in the Midwest region, studies found that 66.8% of participants consumed alcohol, 25.6% smoked, 44.2% did not engage in more than 150 minutes of physical activity per week, and 33.9% were overweight 8 . The consumption of processed foods by students is high, while that of fruits, vegetables, whole grains, and legumes is very low.…”
Section: Introductionmentioning
confidence: 99%
“…Among the risk behaviors for CNCDs in Brazilian university students in health courses in the Midwest region, studies found that 66.8% of participants consumed alcohol, 25.6% smoked, 44.2% did not engage in more than 150 minutes of physical activity per week, and 33.9% were overweight 8 . The consumption of processed foods by students is high, while that of fruits, vegetables, whole grains, and legumes is very low.…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, estudos realizados em países com características distintas de sistemas de ensino e culturas específicas demonstram uma instalação do comportamento de risco à saúde de universitários relacionados à inatividade física, como pode ser comprovado na Hungria (RÁTHONYI e colab.,2021), Estados Unidos (ONG e colab.,2021),China (JIANG e colab., 2021), Nigéria (UGWUEZE e colab., 2021), Itália(TELEMAN e colab., 2015). No entorno sul-americano, a tendência se confirma esta tendência mundial (GARCÍA PUELLO e HERAZOBELTRÁN, 2015) e também no próprio território brasileiro este comportamento de risco é visto na região sul (CRESPO e colab.,2021), no sudeste (TAKENAKA e colab., 2016) e no nordeste (VALENÇA NETO e colab., 2011) e nos estudos que foram publicados em fontes primárias(SOUSA, 2011).Os índices encontrados no atual estudo de inatividade física em estudantes de graduação da área de saúde se assemelham a outro também realizado no centro-oeste brasileiro, que demostraram que a inatividade física de 44,2% da amostra, com maioria feminina, estava relacionada significativamente ao maior índice de morbidades, sobrepeso que eram ampliados pela condição de alimentação inadequada(MONTEIRO e colab., 2021). Também encontra ressonância na realidade nordestina do Brasil, cujos resultados indicam a possibilidade de prevalência de depressão e ansiedade em que a inatividade física é um dos fatores relacionados a este contexto dos acadêmicos envolvidos na pesquisa (LEÃO e colab.,2018).Ainda no Nordeste, o percentual de estudantes da área de saúde que não priorizam a atividade física é de 52,5%.…”
unclassified